2017
DOI: 10.1080/1028415x.2017.1415281
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between dietary quality, serum brain-derived neurotrophic factor (BDNF) level, and the Val66met polymorphism in predicting depression

Abstract: Higher dietary quality was associated with both decreased depression incidence and severity in this cross-sectional analysis. The Val66Met polymorphism did not appear to predict BDNF levels, depression incidence, or modify the relationship between dietary quality and BDNF. Further studies utilizing a larger sample size are needed to confirm this finding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…Furthermore, another study indicated that when Met allele carriers were exposed to a high-CHO diet, their chance of developing carbohydrate-induced hypertriglyceridemia enhanced 49 . In contrast, another study has shown, Val66Met polymorphism did not appear to affect the link between food quality and BDNF serum in terms of depression prediction 50 . Previous research has revealed that dietary intakes alter the relationship between BDNF genotype and obesity-related behaviors, which is corroborated by findings in rats 51 53 .…”
Section: Discussionmentioning
confidence: 74%
“…Furthermore, another study indicated that when Met allele carriers were exposed to a high-CHO diet, their chance of developing carbohydrate-induced hypertriglyceridemia enhanced 49 . In contrast, another study has shown, Val66Met polymorphism did not appear to affect the link between food quality and BDNF serum in terms of depression prediction 50 . Previous research has revealed that dietary intakes alter the relationship between BDNF genotype and obesity-related behaviors, which is corroborated by findings in rats 51 53 .…”
Section: Discussionmentioning
confidence: 74%
“…The BDNF Val66Met (rs6265) genetic variant has been evaluated in several populations, such as Americans [16], Brazilians [26], Argentineans [25], and Malaysians [20]. In these studies, the polymorphic A (Met) allele seems to be somehow related to MDD, either by reducing [16] or raising [21,26] BDNF protein levels or even by increasing the risk [16,20,25] or protection against [23] disease development. Namely, no conformity is present in the literature regarding the rs6265 polymorphism presence and the MDD occurrence.…”
Section: Bdnf Gg (Val/val) Genotype Frequency In Differentmentioning
confidence: 99%
“…When observing only the BDNF Val66Met (rs6265) genetic variant frequency and genotypic distribution (Table 1), the GG (Val/Val) genotype was frequent in more than 50% of the MDD sample studied in 65% of the analyzed studies [17,18,19,21,23,25,26,[30][31][32][33] (Figure 3). Its frequency is lower in only few studies [16,20,22,[27][28][29].…”
Section: Bdnf Gg (Val/val) Genotype Frequency In Differentmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic influence on the development of MDD is indicated by the heritability of between 40 to 75% [16][17][18][19][20][21]. Single nucleotide polymorphisms of a number of genes such as tryptophan hydroxylase-1 (TPH1), tryptophan hydroxylase-2 (TPH2) gene and brainderived neurotrophic factor (BDNF) gene have been associated with MDD [22][23][24][25][26]. A point mutation in the SLC30A3 gene, particularly rs11126936 SNP, has been shown to be associated with schizophrenia in genomewide association studies [27] and low blood zinc levels [28].…”
Section: Introductionmentioning
confidence: 99%